2005
DOI: 10.1111/j.1096-3642.2005.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Halisaurus. from the Late Cretaceous phosphates of Morocco, and the phylogenetical relationships of the Halisaurinae (Squamata: Mosasauridae)

Abstract: A new species of the basal mosasaurid Halisaurus from the Late Cretaceous (Late Maastrichtian) of the Oulad Abdoun Phosphate Basin of Morocco is described on the basis of both cranial and postcranial remains. H. arambourgi sp. nov. is characterized by unique features of the nares, frontal, parietal, girdle and limb bones. A phylogenetical analysis supports the monophyletic status of Halisaurus ; H. platyspondylus (Maastrichtian, New Jersey), H. ortliebi (Maastrichtian, Belgium) and H. arambourgi form an unreso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(79 citation statements)
references
References 21 publications
4
74
0
1
Order By: Relevance
“…We also attribute to Pannoniasaurus a number of isolated teeth (Figures 4H, 5K) that are similar to Halisaurus , i.e., conical and curved posterolingually, bear crowns with fine anastomosing longitudinal striae, and a strong mesial but weaker labiodistal carina [44], [45].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We also attribute to Pannoniasaurus a number of isolated teeth (Figures 4H, 5K) that are similar to Halisaurus , i.e., conical and curved posterolingually, bear crowns with fine anastomosing longitudinal striae, and a strong mesial but weaker labiodistal carina [44], [45].…”
Section: Resultsmentioning
confidence: 79%
“…In all presacral vertebrae of Pannoniasaurus inexpectatus the condyles/cotyles are oval and oblique, and the vertebral condyles are flared ( = precondylar constriction) (most pronounced on juvenile cervicals), in contrast to all known mosasauroids [6], [43], but similar to varanids [46]. The cervicals (Figures 4N, 6A−E) have compressed centra similar to Tethysaurus and Halisaurus [33], [45], [47], and bear small zygosphenes and zygantra. Large crests extend between the synapophyses and anterior edge of the cotyles and project ventrally below the ventral surface of the centrum as in Halisaurus [47], [48] and Tethysaurus [33], and are morphologically similar to the dorsally positioned pterosphenes of palaeophiid snakes [49].…”
Section: Resultsmentioning
confidence: 99%
“…Also, some large sharks that are present in the Maastrichtian of the Paraíba Basin disappeared during the K-P event, but two smaller genera of lamnid sharks crossed the K-P boundary (Gallo et al 2001) and coexisted with G. munizi. It is also interesting to note that dyrosaurids diversified considerably during the Palaeocene, in contrast to the rarity of their remains in the Maastrichtian (Buffetaut 1990;Bardet 1994;Bardet et al 2005). More studies, including detailed stratigraphic work in other basins, particularly in Africa where the Cretaceous-Palaeogene boundary is present as well, might shed more light on the question if the replacement of mosasaurs by dyrosaurids after the K-P transition was a local event or a global trend.…”
Section: Discussionmentioning
confidence: 99%
“…Besides turtles, selachians (Arambourg, 1935(Arambourg, , 1952Cappetta, 1981Cappetta, , 1983Cappetta, , 1984Cappetta, , 1986Cappetta, , 1988Noubhani and Cappetta, 1992, bony fishes (Cavin et al, 2000), and crocodiles (Arambourg, 1952;Buffetaut and Wouters, 1979) were reported from both Maastrichtian and Tertiary beds. In addition, the Maastrichtian beds have yielded mosasaurs and plesiosaurs (Arambourg, 1952;Bardet et al, 2001), dinosaurs (Pereda Suberbiola et al, 2004;Buffetaut et al, 2005), and pterosaurs (Pereda Suberbiola et al, 2003). The nonmarine taxa, assumed to be floated bodies, include a few dinosaurs from the Maastrichtian and mammals from the Tertiary beds (Gheerbrant et al, 1996(Gheerbrant et al, , 1998(Gheerbrant et al, , 2001(Gheerbrant et al, , 2002(Gheerbrant et al, , 2003.…”
Section: Galianemys Emringerimentioning
confidence: 99%